A gap analysis of confined field trial application forms for genetically modified crops in East Africa: evaluating the potential for harmonization - Linacre, Nicholas A.; Cohen, Joel I. (International Food Policy Research Institute, 2006)
The regulatory approval of genetically modified crops in the field initially requires small, restricted experimental trials known as confined field trials. These small scale experiments provide researchers with important information on environmental interactions and agronomic performance of the crop in a safe and contained manner. To authorize confined field trials regulatory review is required, with formats for obtaining relevant information differing from country to country. In this paper, a Gap Analysis is used to identify informational gaps and potential for harmonization of confined field trial application processes in three East African countries - Tanzania, Kenya, and Uganda. The basic principle behind gap analysis is a comparison of the status quo to an ideal with the identification of the differences or gaps and the difficulty involved in removing the gaps. The resulting similarity of the application forms provides a potential basis for harmonization of confined field trial application processes between countries leading to potential efficiency gains.